1997
DOI: 10.1590/s0074-02761997000100007
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Brazilian Populations of Culex quinquefasciatus (Say, 1823) from Endemic and Non-endemic Areas to Infection with Wuchereria bancrofti (Cobbold, 1877)

Abstract: Culex quinquefasciatus is known to be an efficient insect host of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
0
12
0
4
Order By: Relevance
“…quinquefasciatus is limited, and independent of mf density in the blood meal (1 to 3.2 per mosquito). Brito et al (1997) reporting on a study in Maceió e Belo Horizonte found a similar range of L3/mosquito (1.62 and 2.62) after feeding on donor with 450 and 700 mf/ml -1 , respectively. Southgate and Bryan (1992) suggested some limitation to development for filarial infections in Cx.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…quinquefasciatus is limited, and independent of mf density in the blood meal (1 to 3.2 per mosquito). Brito et al (1997) reporting on a study in Maceió e Belo Horizonte found a similar range of L3/mosquito (1.62 and 2.62) after feeding on donor with 450 and 700 mf/ml -1 , respectively. Southgate and Bryan (1992) suggested some limitation to development for filarial infections in Cx.…”
Section: Discussionmentioning
confidence: 63%
“…It has long been recognized that intrinsic difference in the dynamic relationship between W. bancrofti and its vectors necessitates the performance of detailed studies in each endemic area (Samarawickrema & Laurence 1978, McGreevy et al 1982, Lowichich & Lowrie 1988, Brito et al 1997. This study provides the first data of this type for Recife.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…scapularis noted by Macêdo et al (1998). Kartman (1953Kartman ( , 1954, Ramachandan (1970) and Brito et al (1997).…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, there have been reports of vector competence differences between Cx. quinquefasciatus populations isolated from regions with various levels of prevalence of bancroftian filariasis (Janousek & Lowrie 1989, Brito et al 1997, Calheiros et al 1998. Could Cx.…”
mentioning
confidence: 99%